2015
DOI: 10.1038/ncomms7613
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5+ cells regenerate hair cells via proliferation and direct transdifferentiation in damaged neonatal mouse utricle

Abstract: Recruitment of endogenous progenitors is critical during tissue repair. The inner ear utricle requires mechanosensory hair cells (HCs) to detect linear acceleration. After damage, non-mammalian utricles regenerate HCs via both proliferation and direct transdifferentiation. In adult mammals, limited transdifferentiation from unidentified progenitors occurs to regenerate extrastriolar Type II HCs. Here, we show that HC damage in neonatal mouse utricle activates the Wnt target gene Lgr5 in striolar supporting cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(181 citation statements)
references
References 69 publications
9
163
2
Order By: Relevance
“…In this context, Wnt activators have been shown to increase the degree of regeneration after damage (Head et al, 2013;Jacques et al, 2014). Similarly, recent studies of the damaged neonatal mouse utricle revealed that Wnt/β-catenin activation increases both supporting cell proliferation and, subsequently, hair cell regeneration in vivo (Wang et al, 2015). It remains to be tested whether supporting cells in the damaged, adult mammalian cochlea can proliferate and regenerate in response to Wnt/β-catenin activation.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…In this context, Wnt activators have been shown to increase the degree of regeneration after damage (Head et al, 2013;Jacques et al, 2014). Similarly, recent studies of the damaged neonatal mouse utricle revealed that Wnt/β-catenin activation increases both supporting cell proliferation and, subsequently, hair cell regeneration in vivo (Wang et al, 2015). It remains to be tested whether supporting cells in the damaged, adult mammalian cochlea can proliferate and regenerate in response to Wnt/β-catenin activation.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…While the adult mammalian cochlea cannot mount a native regenerative response to HC damage, encouragingly, damaged postmitotic neonatal cochleae and utricles spontaneously regenerate a limited number of HCs by both mitotic regeneration and transdifferentiation [18][19][20]. Likewise, some spontaneous mitotic regeneration and HC production occurs in the adult mouse utricle [21,22].…”
Section: Cell Biology Of Regenerationmentioning
confidence: 99%
“…Both in vivo and in cultured explants, the extent of regeneration in the vestibular epithelium is limited and depends to a large extent on trans-differentiation of SCs (Forge et al, 1998; Forge et al, 1993; Golub et al, 2012; Kawamoto et al, 2009; Slowik et al, 2013; Tanyeri et al, 1995; Wang et al, 2010; Wang et al, 2015; Warchol et al, 1993). In the current study, a small number of Myosin VIIa-positive cells are sparsely detected in the vestibular FE.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian vestibular sensory epithelium undergoes a limited amount of spontaneous hair cell (HC) regeneration after damage (Burns et al, 2012; Forge et al, 1998; Forge et al, 1993; Golub et al, 2012; Kawamoto et al, 2009; Slowik et al, 2013; Tanyeri et al, 1995; Wang et al, 2015; Warchol et al, 1993). The regenerated HCs are largely derived by transdifferentiation of surviving supporting cells (SCs) (Lin et al, 2011; Slowik et al, 2013; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation